Cerebral Haemorrhage in a Young Patient With Atypical Werner Syndrome Due to Mutations in LMNA - Yanhua, Xiao; Suxian, Zhou (Frontiers in Endocrinology, 2018)
Summary Introduction: Werner syndrome is a rare genetic disorder; classical Werner syndrome is caused by mutations in the WRN gene. However, recent research has shown that LMNA gene mutations can also cause premature aging syndromes, such as atypical Werner syndrome (AWS). This usually manifests as muscular damage, defects in the cardiac conduction system, lipoatrophy, diabetes, atherosclerosis, and premature ageing. Clinical presentation: A 24-year-old man presented with severe abdominal aortic and peripheral artery disease and cerebral haemorrhage. He was prescribed once-daily 20 mg atorvastatin. Another large cerebral haemorrhage occurred 8 months after discharge. Molecular studies showed LMNA gene mutations; a missense mutation within exon 5 (c.898G>C) caused amino acid aspartate 300 to be replaced by histidine (p.Asp300His). AWS was diagnosed. Conclusions: Haemorrhagic stroke and progeroid features may be manifestations of LMNA-linked AWS. The patient’s family history and genetic background should be investigated in such cases. WRN and LMNA gene testing of the proband and his immediate family should be considered. This case report provides a deeper understanding of the role of LMNA mutations in AWS.